IMPLEMENTASI INQUIRY-BASEB LEARNING UNTUK KEMAMPUAN BERFIKIR KRITIS PADA SISWA KELAS V MI KANDANG SAPI - Naibaho, Marintan; Nuraini, Intan Siti; Aprilia, Wanda; Aulia, Karmila Nur (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
Inquiry-based learning can improve students' cognitive functions, foster their curiosity, and enhance their ability to solve problems and think analytically. This is the finding of the literature analysis conducted. Contemporary educational goals require students to become critical, creative, and independent learners, so the application of this model is very relevant. The use of IBL is highly dependent on the teacher's understanding of the model steps and the students' readiness to follow the investigation process. IBL has great potential to form a generation that is intelligent, resilient, and ready to face real-world challenges if used correctly. It is hoped that this study will help in creating innovative learning methods in elementary schools. Since elementary education, critical thinking skills are one of the important skills in the twentyfirst century. This study explores the use of the inquiry-based learning (IBL) model in science learning in grade V MI Kandang Sapi and evaluates the effect of the IBL model on improving students' critical thinking skills. The IBL model encourages students to actively participate in the learning process through asking questions, investigating, and drawing conclusions based on facts and information. The teacher acts as a facilitator in the learning process, providing initial stimulus and guiding the path of inquiry.